OPTIMALISASI KREATIVITAS MENGAJAR GURU PADA PEMBELAJARAN IPS GUNAMENINGKATKAN KUALITAS BELAJAR - Riyadini, Sri (WAHANA PEDAGOGIKA, 2016)
This classroom action research aimed to reveal the creativity of teachers to teach in Social studies learning and describe the influence of teachers creativity in teaching Social studies in improving the quality of studentsâ learning to the fourth grade in the first semester of the second state Elementary School Pengumbulanadi, Tikung - Lamongan. This study was designed in the form of the activity cycle. One cycle of activity consisted of four activities, namely: (1) pre - reflection, (2) Planning, (3) The implementation and monitoring, (4) Reflection. From the observation and record activities during PBM of 19 students was able to be obtained significant results in which the value of the results of prior actions gained an average value of 5.5 and after the holding of the action in the numbers with an average value of 7.5. Based on the discussion and analysis for action could be deduced that: the teaching creativity of the teachers at Social studies learning could improve the quality of studentsâ learning at the fourth grade in the first semester of the second state Elementary School Pengumbulanadi, Tikung - Lamongan.